Analisis Pengembangan Sistem Informasi Geografis Visualisasi Data Intelijen Kejaksaan Negeri Lamongan - Ayu Meilinda Puspitasari; Fatwa Ramdani; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Kejaksaan Negeri Lamongan is one of national institute that has authority in law maintenance and justice in Lamongan. One of the aspect to do according to Constitution No.14 2008 about Public Information Openness, that each national institute hast to be able to manage public information to make an easy access for citizen. One of effort that did by Kejaksaan Negeri Lamongan to manifest it is by giving information about the development community dynamist through intelligence data visualization map. To applicate it, there are some obstacle to faced such as history of data that is not well documented, data that is still static, the renewal process that is only done once a year, information that is difficult for the public to access and the inefficient time in managing and visualizing data. Therefore, geographic information system that can manage data and provide data storage is needed. So, it is expected to facilitate and provide the efficiency for Intelligence Section of Kejaksaan Negeri Lamongan to visualizing the data. System development is done by conducting data collection, problem identification, needs analysis, business process modeling, design, implementation and testing. From requirement analysis stage there are 14 functional requirements and a non-functional requirement. The results of system testing indicate that the system has fulfilled user needs, the system is compatible with multiple browsers, it has good performance, and it is easy to use, also system development has a significant effect on the efficiency of the Kejaksaan Negeri Lamongan intelligence's performance by 94%